Оптимизация технологических режимов литья под низким давлением al-mg сплава по критерию максимума жидкотекучести - Чибичик, Ольга Анатольевна; Степаненко, Руслан Николаевич; Горощенко, Александр Николаевич; Гриценко, Дмитрий Викторович; Салтыков, Леонид Александрович; Макаренко, Дмитрий Николаевич (НТУ "ХПИ", 2017)
Проведено математическое моделирование влияния соотношения Al/Mg и температуры на жидкотекучесть Al-Mg сплава. Показано, что такое влияние может быть описано уравнением регрессии в факторном пространстве 2², которое получено на основе реализации центрального ортогонального композиционного плана (ОЦКП) второго порядка. Проанализирована возможность исследования полученной поверхности отклика для выявления оптимальных значений входных переменных, выступающих главными технологическими режимами литья под низким давлением.

An adequate regression equation describing the influence of the Al/Mg ratio and temperature on the Al-Mg alloy castability for low-pressure casting is obtained. It is shown that such effect can be described by the regression equation in the factor space 2², which is obtained on the basis of the realization of the second order central orthogonal compositional design (COCD). The possibility of investigating the received response surface is analyzed to identify the optimal values of the input variables that act as the main technological regimes of low-pressure casting. In particular, it is shown that the study of the nature of the function *(λ) in the four ranges of the input variable separated by the poles λ₁ and λ₂ makes it possible to find the values of the input variables that are suboptimal and provide the possibility of obtaining high castability indices by the appropriate selection of technological regimes - Al/Mg ratio and temperature of the Al-Mg alloy for low-pressure casting.
Optimization of technological modes of low-pressure casting of the al-mg alloy on the castability maximum criterion
Keywords: уравнение регрессии; поверхность отклика; ОЦКП; ЛНД; температура; regression equation; response surface